Analysis of User Readiness and Acceptance of SeaBank Indonesia Using the Technology Readiness and Acceptance Model (TRAM) Approach - Ramadhan, Hibban Daffa; Efrilianda, Devi Ajeng (Journal of Advances in Information Systems and Technology, 2025)
The financial sector has been significantly impacted by informationtechnology, with digital banks emerging to provide services throughdigital platforms. SeaBank Indonesia, a digital bank, offers convenienceslike online account opening, free interbank transfers, and various digitalpayment options. However, some users have reported issues with theapplication, such as login problems and slow processing times.Additionally, some conventional customers remain hesitant to adoptdigital banking due to inexperience and security concerns. This studyaims to explore factors influencing users' adoption of SeaBank Indonesiaby applying the Technology Readiness and Acceptance Model (TRAM).Using a quantitative approach with purposive sampling, the researchcollected 421 valid responses from SeaBank Indonesia users throughonline questionnaires. Data analysis employed partial least squaresstructural equation modeling (PLS-SEM). The results accepted 8 out of12 hypotheses, revealing that intention to use is directly influenced byperceived usefulness, perceived ease of use, and perceived security.Perceived usefulness is directly affected by optimism, innovativeness,and perceived ease of use, while perceived ease of use is directlyinfluenced by optimism and innovativeness. These findings provideinsights into the factors driving digital banking adoption in Indonesia,highlighting the importance of user-friendly interfaces, perceivedsecurity, and technological readiness in shaping users' intentions to usedigital banking applications like SeaBank Indonesia.